Effectiveness of Tailored Multisensory Stimulation Intervention in People with Major Neurocognitive Disorder: A Quasiexperimental Pilot Study - Jèssica Garrido-Pedrosa; Elisabet Capdevila; Núria Berga-Quintana; Loreto González-Román; Maria Eulalia Guijosa-Mira; Irene Astilleros Castro; Jennifer Grau-Sánchez (Hindawi-Wiley, 2024)
Purpose. This study is aimed at evaluating the effectiveness of multisensory stimulation intervention (MSS) on mood, behaviour, quality of life, and physiological parameters in people with major neurocognitive disorder who live in a nursing home. Methods. We conducted a pilot study with a quasiexperimental design. A total of 17 individuals diagnosed with moderate to severe major neurocognitive disorder received eight 30-minute sessions of MSS. Sessions were adapted based on individuals' cognitive level (GDS 6-7) and sensory preferences. Outcomes regarding mood, behaviour, and physiological parameters were collected before and after each session. Outcomes related to quality of life and neuropsychiatric symptoms were assessed pre and postintervention. Results. Participants presented significant improvements in mood and behaviour. They were happier, more attentive to their environment, active/alert, and relaxed/content after sessions. In addition, immediately after their sessions, they were less tearful/sad, fearful/anxious, confused, and wandering/aggressive, as well as less bored/inactive. In terms of physiological parameters, a significant increase in the median heart rate of participants was detected after the sessions, but no differences were found in oxygen saturation. Moreover, a substantial improvement in the participants' quality of life, measured with the quality of life in Alzheimer's disease (p=.03) and in neuropsychiatric symptoms (neuropsychiatric inventory-questionnaire, p=.04), was observed postintervention. Conclusion. MSS appears to be effective on mood and behaviour immediately after sessions and also appears to improve quality of life and reduce neuropsychiatric symptoms postintervention, when these are person-centred through one-to-one interventions that have been adapted to the participants' sensory preferences.